Pengaruh Pemberian Kompensasi Terhadap Prestasi Karyawan: (Studi pada PT Telekomunikasi Indonesia.Tbk. Cabang Langkat) - Safina, Wan Dian; Wirananda, Henny Andriyani (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
Competence of human resources in this study through communication and group collaboration factors that affect the effectiveness of employees at PT. Telkom Indonesia Regional I Sumatra. The data analysis technique used is descriptive and quantitative analysis. The results showed that the Communication and Group Cooperation which had an influence on Employee Work Effectiveness by 77.0% were categorized as very strong. So it can be denied that in measuring the competence of human resources through communication and group factors has a positive and significant influence in supporting the work strength of employees in the company.